Analysis Of Millennial Preferences Between Life Goals And Career Stability In Private Companies - Sitna Hajar, Elvira; Oktavia, Nila; Kohar, Abdul; Nurhakim, Rahman (CITACONOMIA, 2024)
This study examines Indonesian millennials' preferences between pursuing life goals and securing career stability in the private sector. Employing a quantitative approach, it surveyed 400 millennials (born 1981-1996) employed across four sectors: finance, technology, manufacturing, and retail. Data were gathered through an online survey using a validated instrument. Results identify three preference patterns: Pure Purpose-Driven (32%), prioritizing meaning over security; Stability-Dominant (42%), favoring job certainty; and Hybrid (26%), balancing both. Logistic regression (Nagelkerke R² = 0.68) indicates financial pressure as the key determinant, with economically burdened millennials 8.2 times more likely to opt for stability. Family collectivism significantly influences decisions, as 68% of respondents cite family expectations. Sectoral variations are notable, with technology showing higher purpose-driven tendencies. The study refines the